Fatal case of subdural empyema caused by Campylobacter rectus and Slackia exigua - Yuki Munekata; Saki Yamamoto; Shun Kato; Yutaro Kitagawa; Ken Enda; Nanase Okazaki; Satoshi Tanikawa; Zen-ichi Tanei; Yohei Ikebe; Takahiro Osawa; Soichiro Takamiya; Hideki Ujiie; et al. (University of São Paulo, 2023)
We report a fatal subdural empyema caused by Campylobacter rectus in a 66-year-old female who developed acute onset of confusion, dysarthria, and paresis in her left extremities. A CT scan showed hypodensity in a crescentic formation with a mild mid-line shift. She had a bruise on her forehead caused by a fall several days before admission, which initially raised subdural hematoma (SDH) diagnosis, and a burr hole procedure was planned. However, her condition deteriorated on the admission night, and she died before dawn. An autopsy revealed that she had subdural empyema (SDE) caused by Campylobacter rectus and Slackia exigua. Both microorganisms are oral microorganisms that rarely cause extra-oral infection. In our case, head trauma caused a skull bone fracture, and sinus infection might have expanded to the subdural space causing SDE. CT/MRI findings were not typical for either SDH or SDE. Early recognition of subdural empyema and prompt initiation of treatment with antibiotics and surgical drainage is essential for cases of SDE. We present our case and a review of four reported cases.